Intra-Urban Variation of Intimate Partner Violence Against Women and Men in Kenya: Evidence from the 2014 Kenya Demographic and Health Survey. Issue 5 (March 2023) - Ringwald, Beate; Tolhurst, Rachel; Taegtmeyer, Miriam; Digolo, Lina; Gichuna, Grace; Gaitho, Mwangi Michael; Phillips–Howard, Penelope A.; Otiso, Lilian; Giorgi, Emanuele
Although urban areas are diverse and urban inequities are well documented, surveys commonly differentiate intimate partner violence (IPV) rates only by urban versus rural residence. This study compared rates of current IPV victimization among women and men by urban residence (informal and formal settlements). Data from the 2014 Kenya Demographic and Health Survey, consisting of an ever-married sample of 1, 613 women (age 15–49 years) and 1, 321 men (age 15–54 years), were analyzed. Multilevel logistic regression was applied to female and male data separately to quantify the associations between residence and any current IPV while controlling for regional variation and other factors. Results show gendered patterns of intra-urban variation in IPV occurrence, with the greatest burden of IPV identified among women in informal settlements (across all types of violence). Unadjusted analyses suggest residing in informal settlements is associated with any current IPV against women, but not men, compared with their counterparts in formal urban settlements. This correlation is not statistically significant when adjusting for women's education level in multivariate analysis. In addition, reporting father beat mother, use of current physical violence against partner, partner's alcohol use, and marital status are associated with any current IPV against women and men. IPV gets marginal attention in urban violence and urban health research, and our results highlight the importance of spatially disaggregate IPV data—beyond the rural-urban divide—to inform policy and programming. Future research may utilize intersectional and syndemic approaches to investigate the complexity of IPV and clustering with other forms of violence and other health issues in different urban settings, especially among marginalized residents in informal urban settings.